Tinjauan Fiqih Siyasah terhadap Lembaga Yudikatif di Indonesia - Mohamad Bagas Rio R; Rahma Kemala Dewi; Sely Agustina (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2021)
In modern times Siyasah Idariyah is a way to achieve good governance. The study of Siyasah Idariyah is related to government including authorities, organs, agencies, government public bodies and so on. State power that controls all areas of the life of a sentalistic state in one power will produce ineffective and efficient results and even tend to deviate from the constitution and applicable regulations. For this reason, this fact encourages philosophers to seek solutions regarding the distribution of power so that it is evenly distributed and does not accumulate in one person or institution of power. The thought that was born by these philosophers was one of them in the form of the Trias Politica theory. This theory states that state power needs to be separated into three parts, namely Legislative, Executive and Judicial powers. The basic sources of Siyasah Idariyah are sourced from the Qur'an and hadith as well as ijma and qiyas and so on.